The Japanese Labor Market During the COVID- 19 Pandemic - Kotera, Shinya; Schmittmann, Jochen M. (Washington, D.C. : International Monetary Fund, 2022)
This paper investigates labor market dynamics in Japan during the COVID-19 pandemic drawing on macro and micro data. The pandemic and related containment measures had a large negative impact on employment, labor force participation, earnings, and labor market mobility, although policy support through furlough schemes partially mitigated the rise in unemployment. Our results indicate that industry effects were a crucial driver of labor market outcomes for different groups of employees - women, younger age groups, nonregular, self-employed, and low-income workers accounted for a disproportional share of employment in the hardest hit industries. We also find empirical evidence for the need to improve childcare and related support, training and upskilling offerings, and teleworking availability, and the role of skill mismatches in reducing labor market mobility and resource reallocation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Employment; Intergenerational Income Distribution; Macroeconomics; Unemployment; Wages